2021
DOI: 10.3390/nano11092184
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Distribution of Poly(ethylene glycol) Functionalized Iron Oxide Nanoclusters: An Ultrastructural Study

Abstract: The in vivo distribution of 50 nm clusters of polyethylene glycol-conjugated superparamagnetic iron oxide nanoparticles (SPIONs-PEG) was conducted in this study. SPIONs-PEG were synthesized de novo, and their structure and paramagnetic behaviors were analyzed by specific methods (TEM, DLS, XRD, VSM). Wistar rats were treated with 10 mg Fe/kg body weight SPIONs-PEG and their organs and blood were examined at two intervals for short-term (15, 30, 60, 180 min) and long-term (6, 12, 24 h) exposure evaluation. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…The results were in accordance with other studies, where PEG-coated nanoparticles (less than 50 nm) showed saturation magnetization (Ms) of 23 emu/g with Mr values less than 2 nm [ 45 , 46 ]. Another study with a similar size distribution of PEG-coated nanoparticles (50–300 nm) also showed superparamagnetic behavior with a coercivity value of 27 Oe and an Mr of 2.2 [ 47 ]. The current study with a particle size of 190 nm showed a coercivity of 19.06 Oe and an Mr of 0.125 emu/g.…”
Section: Resultsmentioning
confidence: 98%
“…The results were in accordance with other studies, where PEG-coated nanoparticles (less than 50 nm) showed saturation magnetization (Ms) of 23 emu/g with Mr values less than 2 nm [ 45 , 46 ]. Another study with a similar size distribution of PEG-coated nanoparticles (50–300 nm) also showed superparamagnetic behavior with a coercivity value of 27 Oe and an Mr of 2.2 [ 47 ]. The current study with a particle size of 190 nm showed a coercivity of 19.06 Oe and an Mr of 0.125 emu/g.…”
Section: Resultsmentioning
confidence: 98%
“…Dehydrated samples were then embedded in Epon 812 resin, gradually, using Epon in acetone solutions at ratios of 1:3, 1:2; 1:1, 2:1, and 3:1 (1 h each step)m alogn with pure Epon (overnight). Embedded samples were placed in plastic capsules and left to cure at 60 °C for 2–3 days until hard (polymerized) [ 17 ]. Capsules were then cut off, the hardened samples were trimmed and sectioned using Leica UC7 Ultramicrotome, obtaining 150 nm and 50–90 nm thick sections.…”
Section: Methodsmentioning
confidence: 99%
“…Sorted by crystalline features, metal NMs could be classified into representative references, based on pure-phased crystalline such as nanoparticles (NPs) with highly crystalline properties and metal clusters formed by atoms aggregations [ 9 ]. When their properties were evaluated in physicochemical works, metal clusters drew the most interest among composite materials due to their unique characteristics [ 10 , 11 , 12 , 13 ]. Nanoclusters consisting of fewer atoms have a higher specific surface area, which might perform the promised function actively.…”
Section: Introductionmentioning
confidence: 99%